2006
DOI: 10.1007/s00595-006-3282-x
|View full text |Cite
|
Sign up to set email alerts
|

Resection of Over 290 Polyps During Emergency Surgery for Four Intussusceptions with Peutz–Jeghers Syndrome: Report of a Case

Abstract: A 41-year-old male patient with aggravated epigastralgia and nausea was admitted to Central Aizu General Hospital in February 1997. His past history showed a colonic polyp and anemia in the fourth decade. The patient looked healthy, but showed abdominal distension and tenderness, and pigmented lips. A plain abdominal X-ray revealed a dilation of the small intestine with niveau. Computed tomography disclosed multiple target signs. An emergency laparotomy clarified four intussusceptions of the small intestine wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Some consider these polyps as premalignant lesions, which should be paid considerable attention and removed by surgery or endoscopy. However, others found out that rate of cancer in these polyps is very low, so periodic endoscopic surveillance is enough [ 5 , 10 , 11 ]. As a limitation in this case report, there was not mutation analysis to find out a defect in the STK11 gene is responsible for the PJS phenotype in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…Some consider these polyps as premalignant lesions, which should be paid considerable attention and removed by surgery or endoscopy. However, others found out that rate of cancer in these polyps is very low, so periodic endoscopic surveillance is enough [ 5 , 10 , 11 ]. As a limitation in this case report, there was not mutation analysis to find out a defect in the STK11 gene is responsible for the PJS phenotype in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical resection is recommended, there is still no consensus regarding optimal management of adult intussusception 3,19,21 . Definitive surgical resection remains the recommended treatment in most cases of PJS associated with intussusception because of the large proportion of structural causes and the relatively high incidence of malignancy 19,[22][23][24][25] . Previous studies have also shown that the majority of the patients suffer from recurrent episodes of intussusception induced by polyps who require laparotomy 5,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Definitive surgical intervention is recommended in PJS patients complicated by intestinal obstruction, evidence of malignancy, or considerable gastrointestinal hemorrhage[ 10 - 12 ]. In our case, the patient was complicated by intestinal obstruction caused by intussusceptions due to intestinal polyps.…”
Section: Discussionmentioning
confidence: 99%